Students' perceptions about conflict in the area of southernmost of Thailand - Thongpoon, Kumpee; Harun, Azhar; Thongpoon, Siriluck; Chaiyakhet, Wachara (2016)
This is a research paper which describe about students' perceptions about conflict in the area of southernmost of Thailand.Which have the objectives that what are the causes of problems? What are the obstacles of problems solving? And also what are the possible ways.That conflict can decrease? This research set the interview forms to ask students and let them talk and comment the three questions. This research found that there are many people misunderstand about the way that to solve conflict. The official staffs also have conflict inside the area that is a key factor to solve conflict.